Comprometimento organizacional: correlatos valorativos e organizacionais - Lima, Carla Fernanda de (2017)
having as explanatory variables the organizational climate, work satisfaction, and human values. Study 1 intended to develop a theoretical model of organizational commitment having as independents variables organizational climate, work satisfaction and human values. . 303 employees from public and private companies of 18 Brazilian states participated, with mean age of 32 years (SD = 8.56), most were female (61.4%), single (47.2%), and with no children (65%). Participants answered an online questionnaire composed by four measures: Organizational Behavior Scale (BOBS), Organizational Climate Scale (OCS), Work Satisfaction Scale (WSS), and Basic Values Survey (BVS). Results indicated that personal (excitement and promotion) and social values (interactive and normative), organizational climate, and work satisfaction are antecedents of the organizational commitment. Study 2 aimed to test a theoretical model of organizational commitment in a private institution having as independents variables personal and social values, organizational climate and work satisfaction. Participants were 270 employees in a private institution of João Pessoa (PB), with mean age of 29.7 years (SD = 9.17), most were female (68.2%). Results showed that the most adequate model had the organizational commitment explained by personal (excitement and promotion) and social values (interactive and normative), organizational climate, and work satisfaction. Study 3 intended to replicate an explanatory model of organizational commitment in a public institution. Participants were 237 employees of a public institution in João Pessoa (PB), with mean age of 40 years (SD = 11.78), most were male (54.9%), married (50.4%), without children (55.7%), and with postgraduate level of study (42.6%).Results showed that the model developed for the private institution was also adequate for the public institution, with better adjustment indexes, nevertheless, it was had a modification between personal values and commitment. These findings were discussed based on of the nature of private and public services, attempting to understand the function of similar institutions and their impact on organizational commitment. It was concluded with a proposal of an organizational commitment an explanatory model, based on human values, organizational climate and job satisfaction. Considering potential limitations of the studies, it was suggested future research that could increase knowledge of organizational commitment.